2017
DOI: 10.1177/0265407517737387
|View full text |Cite
|
Sign up to set email alerts
|

Withdrawal, attachment security, and recovery from conflict in couple relationships

Abstract: This study used 115 cohabiting couple partners' 21-day diaries, with which they reported each evening on their moods and their relationships, to test hypotheses about connections between withdrawal following conflict, attachment insecurity, and affective recovery from conflict (i.e., post-conflict relationship satisfaction, positive and negative mood, and intimacy). Individuals reported on their own and their partners' post-conflict withdrawals. Results indicated that individuals who withdrew following conflic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 52 publications
4
19
0
Order By: Relevance
“…However, the destructive responses and poor interaction outcomes associated with attachment insecurity are likely to carry forward to impact subsequent nonconflictual interactions and thus interfere with couples' ability to share positive experiences (Table 3). This type of conflict spillover is typically examined by assessing how the experiences and responses within couples' conflict interactions transfer to responses within subsequent non-conflict interactions 74,[76][77][78][79] .…”
Section: Spillover Of Romantic Attachmentmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the destructive responses and poor interaction outcomes associated with attachment insecurity are likely to carry forward to impact subsequent nonconflictual interactions and thus interfere with couples' ability to share positive experiences (Table 3). This type of conflict spillover is typically examined by assessing how the experiences and responses within couples' conflict interactions transfer to responses within subsequent non-conflict interactions 74,[76][77][78][79] .…”
Section: Spillover Of Romantic Attachmentmentioning
confidence: 99%
“…Thus, rather than displaying hostility, avoidant individuals are less likely to engage in repair efforts or be responsive to their partner's repair efforts following conflict 79 . Disengagement and lack of effort to maintain relationships frequently trigger adverse reactions from partners, as evidenced by partners of individuals high in avoidance exhibiting greater negativity and perseveration on conflict in subsequent couple interactions than partners of individuals low in avoidance 76,78,79 .…”
Section: Spillover Of Romantic Attachmentmentioning
confidence: 99%
See 1 more Smart Citation
“…We crafted a checklist that (a) allows couple partners themselves to identify what they do to reconcile day-to-day and (b) identifies dimensions of postconflict reconciliation strategies that can be used to determine which strategies are most closely associated with recoveries after conflict. Prager et al (2015Prager et al ( , 2019 defined affective recovery from conflict as a two-step process: (a) the individual partners return to a neutral or positive emotional state; angry or frustrated arousal subsides; and (b) the couple reestablishes their bond via intimate relating (either verbally or through other intimacy-promoting behavior). We identified residual, negative changes in affect, intimacy, and satisfaction following conflict as inverse indicators of postconflict recovery.…”
mentioning
confidence: 99%
“…Totenhagen, Randall, and Lloyd (2018) found that the more severe a conflict was within a romantic relationship, the lower the overall perceived relationship quality was between the individuals. Similarly, other researchers have found that when RRCs are more serious or appear to be unresolvable, the partners involved are more likely to withdraw from that conflict (Prager, Poucher, Shirvani, Parsons, & Allam, 2019). This can result in decreased relationship quality.…”
Section: Romantic Relationship Conflictsmentioning
confidence: 80%